Hybrid System in Foil Containing Secure Identification and Temperature Sensing Units - Scholz, Alexander; Alam, Shawon; Hadrich, Wacime; Schroder, Andre; Wolfer, Tim; Friedrich, Martin; Kister, Thomas; Lay, Makara; Sauva, Sophie; Passlack, Ulrike; Campana, Manuel; Koker, Liane; et al. (IEEE journal on flexible electronics, 2025)
Flexible hybrid electronics allow for seamless integration of sensing functionalities within materials, nonconformal surfaces, and products, and thus can enable novel value chains. Next to new functionalities, product authenticity plays a crucial role in complex global supply chains. This holds especially true, when products are deployed in critical environments, such as the industrial or automotive sector, where product failure can be fatal. In this work, we present a secure hybrid system, which contains a custom-designed, thinned application-specific integrated circuit (ASIC) in foil, as well as two printed temperature sensing elements that are seamlessly embedded in an industrial process fabricated automotive coolant hose and an inkjet-printed unique identifier in the form of a physically unclonable function (PUF) to derive the system's authenticity. We show the results of the standalone hose-integrated temperature sensors, the bulk ASIC verification results prior to thinning and foil integration, and the fully assembled integrated hybrid system. The thinned ASIC in foil communication interfaces, its circuit building blocks, and the integrated printed components were successfully commissioned. We show the obtained temperature response and the unique identification by generating the challenge-response pairs (CRPs) of the PUF over 1000 repetitions. The security circuit shows only 0.0084% of flipped bits at T = {25}~^{° } C, which makes it well-suited to be used as PUF.